If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -2(x + 3) = 9 Reorder the terms: 17 + -2(3 + x) = 9 17 + (3 * -2 + x * -2) = 9 17 + (-6 + -2x) = 9 Combine like terms: 17 + -6 = 11 11 + -2x = 9 Solving 11 + -2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -2x = 9 + -11 Combine like terms: 11 + -11 = 0 0 + -2x = 9 + -11 -2x = 9 + -11 Combine like terms: 9 + -11 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| -6x-46=-11x+74 | | (1+2x)/7+(5-x)/3=37/21 | | .11k+1.5=2.4 | | 19.79+0.8-12.3c=-19.71-14.9c | | 5x-6(x+3)=15 | | 3x-7+2x+4-7x= | | -79+x=54+8x | | a/7+5/7+2/7 | | 8b-0.5=9b | | -190-2x=-10x+50 | | y-12=-3 | | Y+2=5y-6 | | 8-9(k-3)=14k-11 | | b/5=19 | | x^2+14x=-20 | | 5x^2=2x-7 | | 4x-5(x+3)=16 | | 4+x=-13 | | 5x+21=2x+15 | | -2.86-17.1t=5.24-15.3t | | 5x+6=x+22 | | 1/3(2x+4)+5=-2/3(x+1) | | 6.25x+12=30.75 | | 2/3(4x-10) | | 9v-6=5v+18 | | (6x+15)/4=-15x-25+(5/4) | | 8-9(3-k)=14k-11 | | 10[3p+4]-1=49 | | 1/3(2x-1)+1/4(1/2-3x)=-2 | | 5x+21=2x+25 | | 8y-5y-15=32.79 | | 6.25x+12x=30.75 |